La tecnificación como herramienta para incrementar la productividad agropecuaria en Colombia (2019)
Technification has shown that its correct use allows increasing the productivity of an economic activity or of a complete sector. That is why it is the central axis of this work. Colombia has been characterized by the informality of work in the countryside together with the little use of technologies, which has affected competitiveness and the efficient use of agricultural production in the country. The applied technology will be developed in the course of the text, showing the latest advances in science and technology within the agricultural sector in Colombia. The flagship products are the priority within a primary sector with little investment in alternative crops that can represent a considerable market, given the diversity of the country in the agricultural sector. An analysis of the evolution of the primary sector within our country will explain with statistics, the resources that Colombia has. In addition, a comparison with the main powers of the world will show the capacities and limitations present in the agricultural sector of Colombia, this is where the technification will play the crucial role to represent a growth and development in the national and international market, generating great benefits to the Colombian economy, agricultural producers and consumers. The transfer of technology and knowledge will be the vehicle that will achieve the desired rates in terms of productivity and competitiveness, making efficient use of the resources that already have and adding the use of technology can allow inefficient crops to achieve considerable figures In addition, the diversification of the agricultural sector will be strengthened.